Calcium phosphate nanocarriers for drug delivery to tumors: imaging, therapy and theranostics. (15th August 2019) - Huang, Dan; He, Bin; Mi, Peng
Abstract : This paper has reviewed the recent advances in the development of CaP nanocarriers and their applications in tumor diagnosis, gene delivery, drug delivery and theranostics and finally discussed the perspectives. Abstract : Calcium phosphate (CaP) was engineered as a drug delivery nanocarrier nearly 50 years ago due to its biocompatibility and biodegradability. In recent years, several approaches have been developed for the preparation of size-controllable, stable and multifunctional CaP nanocarriers, and several targeting moieties have also been decorated on the surface of these nanocarriers for active targeting. The CaP nanocarriers have been utilized for loading probes, nucleic acids, anticancer drugs and photosensitizers for cancer imaging, therapy and theranostics. Herein, we reviewed the recent advances in the preparation strategies of CaP nanocarriers and the applications of these nanocarriers in tumor diagnosis, gene delivery, drug delivery and theranostics and finally provided perspectives.